PENGARUH PERUBAHAN HARGA LADA TERHADAP KESEJAHTERAAN PETANI LADA KELOMPOK TANI MEGA BUANA DI DESA BATUAH KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA - Ajeng Priantari; Nur Hidayat; Rossy Mirasari (Politeknik Pertanian Negeri Samarinda, 2020)
In Batuah Village, production of pepper has decreased due to land fires, land conversion to the mining sector and changes in other crop commodities and the price of pepper which is always changing and tends to decline. The welfare of farmers can be realized starting from increased income, increased production, and high purchase prices. The factor that causes farmers to feel less prosperous and not yet developed is that the price of pepper is bought cheaply by middlemen or collectors. The purpose of this study was to determine the characteristics of pepper farmers and whether there is an effect of changes in pepper prices on farmer welfare. The results showed that rcount <rtabel (-0.331 <0.396), and it can be concluded that there is a very weak influence between the effect of price and the welfare of pepper farmers. It can be assumed that it is not only pepper plants that are planted by pepper farmers so that pepper farmers do not depend only on the commodity of the pepper plant.